Analysis of carotenoids in edible flowers of Dianthus chinensis processed by ionizing radiation (Brazilian Journal of Radiation Sciences, 2021)
The tendency to use edible flowers in gastronomy to add beauty, color, and flavor in food preparation has been increasing in recent years. Several species have active biological substances, which play an important role in health maintenance. This highly perishable food should be grown without the use of pesticides. Thus, several methods are applied to increase the shelf life of food products, as well as ensure their quality and safety. Among the treatments, the food irradiation process has proven to be an effective tool in preserving and extending the shelf life of the perishable product. Dianthus chinensis flowers, popularly known as chinese pink (cravina), belongs to the family Caryophyllaceae, are native to Asia and Europe, are widely used in culinary preparations, is also acknowledged for their bioactive components and antioxidant properties. The purpose of this study was to evaluate carotenoids in D. chinensis flowers submitted to gamma irradiation and electron beam doses of 0.5, 0.8, and 1.0 kGy. High performance liquid chromatography was used to carotenoids determination. In the specie of edible flowers analyzed it was found carotenoid lutein (4.02 to x 7.52 mg/ 100 g). In general, the lutein was higher for irradiated samples, especially those treated with 0.8 and 1.0 kGy independently of irradiation technology. Accordingly, the applied irradiation treatments seemed to represent a feasible technology to preserve the quality of edible flower petals.